2021
DOI: 10.1186/s12951-021-00904-6
|View full text |Cite
|
Sign up to set email alerts
|

The targetable nanoparticle BAF312@cRGD-CaP-NP represses tumor growth and angiogenesis by downregulating the S1PR1/P-STAT3/VEGFA axis in triple-negative breast cancer

Abstract: Background Overexpressed vascular endothelial growth factor A (VEGFA) and phosphorylated signal transducer and activator of transcription 3 (P-STAT3) cause unrestricted tumor growth and angiogenesis of breast cancer (BRCA), especially triple-negative breast cancer (TNBC). Hence, novel treatment strategy is urgently needed. Results We found sphingosine 1 phosphate receptor 1 (S1PR1) can regulate P-STAT3/VEGFA. Database showed S1PR1 is highly express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Given the recent findings that S1P1 is important for TNBC survival [ 22 , 23 ], we next performed a Western blot analysis to assess the protein levels of S1P1 in a panel of human TNBC and less aggressive luminal breast cancer cell lines, as well as a nontransformed breast epithelial cell line (MCF10A) ( Figure 1 d). Consistent with our transcript findings, we did not detect significant differences in total S1P1 protein levels between TNBC and luminal breast cancer cells ( Figure 1 e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the recent findings that S1P1 is important for TNBC survival [ 22 , 23 ], we next performed a Western blot analysis to assess the protein levels of S1P1 in a panel of human TNBC and less aggressive luminal breast cancer cell lines, as well as a nontransformed breast epithelial cell line (MCF10A) ( Figure 1 d). Consistent with our transcript findings, we did not detect significant differences in total S1P1 protein levels between TNBC and luminal breast cancer cells ( Figure 1 e).…”
Section: Resultsmentioning
confidence: 99%
“…In the context of breast cancer, high S1P1 levels correlate with rapid recurrence rates, shorter survival times, and increased resistance to tamoxifen in ER-positive breast cancer patients [ 21 ]. Emerging evidence revealed that several experimental treatments can kill TNBC by downregulating S1P1 signaling, suggesting its importance in TNBC survival [ 22 , 23 ]. Hence, it is crucial to apply animal models to gain an in-depth understanding of this receptor in TNBC pathogenesis to guide therapeutic selection.…”
Section: Introductionmentioning
confidence: 99%
“…The CD8 and CD4 T cells are the key components of the cancer microenvironment, which is strongly related to the occurrence and development of cancer [ 34 , 35 ]. An increasing number of studies has found that not only the immune cells but also the stromal cells play important roles in the progression and prognosis of tumors [ 36 , 37 , 38 , 39 ]. For example, the osteoblasts, the first bone-resident cells identified to regulate hematopoiesis, were posited as the remote regulators of lung cancer [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the radical-containing nanoparticles increased the anti-angiogenic activity in breast cancer [ 112 ]. In the study of Gong et al [ 113 ], nanoparticles delivering a sphingosine-1 phosphate receptor inhibitor drastically inhibited triple negative breast cancer growth and angiogenesis in vivo. Summary of the described data is included in Table 2 .…”
Section: Possible Utility Of the Vegf Family Members In Breast Cancermentioning
confidence: 99%